2003
DOI: 10.7557/3.2748
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the harbour porpoise (<i>Phocoena phocoena</i>) in eastern Newfoundland, Canada

Abstract: Although the stock relationships among harbour porpoise (Phocoena phocoena) in the Northwest Atlantic are unknown, it has been postulated that there are 4 local populations: Bay of Fundy/Gulf of Maine, Gulf of St. Lawrence, Newfoundland, and west Greenland. Data on the Newfoundland population are extremely limited. To determine growth rates and examine if these animals can be differentiated from other sub-populations on the basis of growth characteristics, 94 porpoises caught incidentally in fishing gear along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The distribution of catch reports confirms that harbour porpoises are only present during the summer and fall months in waters around the island of Newfoundland (Richardson, 1992; Fig. 2).…”
Section: Estimated Small Cetacean Incidental Catch In 2001-03supporting
confidence: 67%
“…The distribution of catch reports confirms that harbour porpoises are only present during the summer and fall months in waters around the island of Newfoundland (Richardson, 1992; Fig. 2).…”
Section: Estimated Small Cetacean Incidental Catch In 2001-03supporting
confidence: 67%
“…, Richardson et al . ). A single Gompertz growth curve was used in the current study, as asymptotic values obtained from this plot were thought to be sufficient for assessing if individuals had attained a stable adult size (after Murphy and Rogan ).…”
Section: Discussionmentioning
confidence: 97%
“…Information on vital parameters are available from a number of regions including the Gulf of Maine/ Bay of Fundy (Fisher and Harrison 1970, Read and Gaskin 1990, Read and Hohn 1995, Newfoundland (Richardson 1992, Richardson et al 2003, Greenland (Kinze et al MS 1990, Norway (Bjørge et al 1991), Denmark (Møhl-Hansen 1954, Clausen and Andersen 1988, Sorensen and Kinze 1994, Lockyer and Kinze 2003, Germany (Benke et al 1998), The Netherlands (Addink et al 1995), Ireland (Rogan and Berrow 1995), United Kingdom (Lockyer 1995a), Spain (Lens 1997), Portugal (Sequeira 1996), andWest Africa (Smeenk et al 1992). The available data on population parameters of harbour porpoise in the North Atlantic are reviewed by Lockyer (2003).…”
Section: Biological Parametersmentioning
confidence: 99%
“…Many studies have found that these samples are biased towards younger animals and/or unequal sex ratios (e.g. IWC 1991, Richardson et al 2003, Sørensen and Kinze 1994, Lockyer 1995b). Such samples can provide an indication of vital parameters that can be used as a starting point or for comparisons between samples, but caution must be used as they may exhibit unknown biases that could affect the estimates of the age structure, sex ratios and/or reproductive status of the population (Donovan and Bjørge 1995).…”
Section: Biological Parametersmentioning
confidence: 99%
See 1 more Smart Citation